2019
DOI: 10.3390/ijerph16132305
|View full text |Cite
|
Sign up to set email alerts
|

LGBT+ Health Teaching within the Undergraduate Medical Curriculum

Abstract: : Introduction: The lesbian, gay, bisexual, and transgender (LGBT+) population experience health and social inequalities, including discrimination within healthcare services. There is a growing international awareness of the importance of providing healthcare professionals and students with dedicated training on LGBT+ health. Methods: We introduced a compulsory teaching programme in a large London-based medical school, including a visit from a transgender patient. Feedback was collected across four years, befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 17 publications
1
54
0
Order By: Relevance
“…Training programs that provide exposure to LGBT patients can increase medical students' comfort levels in caring for this population [6]. Likewise, LGBT education programs can increase knowledge [6] and confidence in clinical assessments [7] of LGBT people among medical students. Over the past decade, many medical schools have made efforts to include LGBT-specific healthcare topics in their curricula.…”
Section: Introductionmentioning
confidence: 99%
“…Training programs that provide exposure to LGBT patients can increase medical students' comfort levels in caring for this population [6]. Likewise, LGBT education programs can increase knowledge [6] and confidence in clinical assessments [7] of LGBT people among medical students. Over the past decade, many medical schools have made efforts to include LGBT-specific healthcare topics in their curricula.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Instructional methods Primarily, instructional methods in our survey were lectures, and only one school provided a workgroup in which students discussed sexual minority issues. However, feedback processes are an essential part of instruction for quality improvement of education [50]. For example, one medical school in London utilized feedback to assess the initial lecture regarding sexual orientation, and for the following lecture, they succeeded Table 6.…”
Section: Methodsmentioning
confidence: 99%
“…in expanding the program based on the feedback from students [50]. Feedback takes many forms, providing an evaluation of the educational process with student responses to surveys, or providing a student with feedback as a result of programmatic assessments [33,51].…”
Section: Overall Goalsmentioning
confidence: 99%
“…Many scholars also require medical education to instill correct knowledge of and positive attitudes toward LGBT+ into medical students or healthcare professionals [14][15][16][17][18][19][20]. Many studies revealed the importance of teaching medical students to understand basic LGBT+ concepts and terminology and focused on guiding students toward establishing friendly attitudes toward LBGT+ in their courses [18,19], including inviting LGBT+ community members to participate in curriculum development, lesson planning, or teaching assistance [18]. Some studies demonstrated multiple approaches to providing students with teaching on LGBT+ health in medical education curricula, such as didactic lectures, student-led presentations, patient panels, and small-group sessions [17,20].…”
Section: Competency-based Medical Education and Gender Competencymentioning
confidence: 99%
“…Salkind, Gishen, Drage, Kavanagh, and Potts introduced a compulsory curriculum in a medical school to provide undergraduate students with LGBT+ health-related education, including talks from transgender patients as guest speakers. The respective research results showed that students learned to use appropriate language to explain and discuss sexual orientation and gender identity [18].…”
Section: Competency-based Medical Education and Gender Competencymentioning
confidence: 99%